Degenerations of k-positive surface group representations - Beyrer, Jonas; Pozzetti, Maria Beatrice (Journal of topology, 2024)
We introduce k\k\-positive representations, a large class of 1,…,k\łbrace 1,łdots ,k\rbrace\-Anosov surface group representations into PGL(E)\mathsf PGL(E)\ that share many features with Hitchin representations, and we study their degenerations: unless they are Hitchin, they can be deformed to non-discrete representations, but any limit is at least (k−3)\(k-3)\-positive and irreducible limits are (k−1)\(k-1)\-positive. A major ingredient, of independent interest, is a general limit theorem for positively ratioed representations.
Erstveröffentlichung: 3. August 2024
Gesehen am 28.04.2024